Development of mixed matrix sulfonated polysulfone and polyethersulfone for proton exchange membrane fuel cell application - Mohd Shamim Waliyuddin, Rosman (2009)
The objective of this study was to prepare a mixed matrix of sulfonated polysulfone (SPSU) and polyethersulfone (PES) and investigate its potential for proton exchange membrane fuel cell (PEMFC) application. Four samples were prepared in this study, a sample of PSU/PES as a reference and 3 other samples SPSU/PES with the amount of sulfonating agent (trimethylsilyl chlorosulfonate, TMSCS) varied for each sample (10mL, 15mL and 20mL). The sulfonated membrane samples (SPSU/PES 1, SPSU/PES 2 and SPSU/PES 3) were prepared in 20 hours stirring time, 10 minutes of TMSCS dropwise time and 15 minutes of sodium methoxide dropwise time. FTIR test confirmed that the sulfonation process was successful for all three sulfonated samples where wavelength of 1029.27 cm-1 detected for sample SPSU/PES 1, 1035.75 cm-1 for sample SPSU/PES 2 and 1031.52 cm-1 for sample SPSU/PES 3. Referring to water/methanol mixture uptake test, sample SPSU/PES 3 had the highest swelling degree with the amount of 62.93% followed by SPSU/PES 2 (58.95%), SPSU/PES 1 (46.9%) and PSU/PES (33.43%). Elemental analysis was done in order to obtain data for degree of sulfonation calculation. From the calculation, it was found that sample SPSU/PES 3 has the highest degree of sulfonation (72.53%) followed by SPSU/PES 2 (55.49%) and SPSU/PES 1 (38.46%).